Development and Validation of AgTech-Enabled Market Access Scale for Hi -Tech Agriculture - S, Sownthariya; Safna Vatakke Kandy Meethal,; Allan Thomas, (Indian Journal of Extension Education, 2025)
Digital technologies and institutional innovations are increasingly shaping agricultural market access alongside traditional infrastructure. This study, conducted in 2025, developed and validated a multidimensional scale to systematically measure farmers’ perceptions of AgTech-enabled market access in hi-tech cultivation. The validated scale consisted of 56 items across nine dimensions: transportation infrastructure, distance to market, market information access, digital market platforms, agri-input accessibility, market institutions, storage and logistics, intermediaries, and frequency of market visits. Empirical validation demonstrated high conformity (mean = 13.64), strong relevancy ratings (>3.0), high internal consistency (Cronbach’ alpha value = 0.97), and significant dimensional distinctiveness (ANOVA, F = 3.301; p < 0.01). The mean value of Simpson’s Index of Diversity was found to be 0.834, indicating the diverse nature of the scale items across the nine dimensions. The scale provides a robust and reliable instrument for researchers, policymakers, and extension professionals to assess AgTech-enabled market access, identify barriers, and design evidence-based interventions for strengthening hi-tech agriculture.